2019
DOI: 10.1021/acs.jpcc.8b12527
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Stabilized High-Energy-Density Alkaline-Earth-Metal Pentazolate Salts

Abstract: Polynitrogen compounds especially pentazolate anion complexes recently have attracted substantial attention due to their promising potential as high-energy-density materials. Here, using a machine-learning-accelerated crystal structure search method and first-principles calculations, we predict a new hybrid compound by inserting a large fraction of nitrogen into alkaline-earth metals. It is a new stoichiometric type MN10 (M = Be, Mg), which possesses a metal-centering octahedral pentazolate framework with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 62 publications
0
83
1
Order By: Relevance
“…1), which are arranged in exotic planar infinite zigzag N-N chains parallel to the a -axis, akin to those found in FeN 4 and ReN 8 · x N 2 near 110 GPa 13,14 . While the MgN 4 compound’s crystal chemistry matches the theoretical calculations 1719 , the measured lattice parameters do not, as the c parameter is double the predicted value and the structure adopts an I -type unit cell, opposite to the calculated C -type (see Supplementary Discussion). As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…1), which are arranged in exotic planar infinite zigzag N-N chains parallel to the a -axis, akin to those found in FeN 4 and ReN 8 · x N 2 near 110 GPa 13,14 . While the MgN 4 compound’s crystal chemistry matches the theoretical calculations 1719 , the measured lattice parameters do not, as the c parameter is double the predicted value and the structure adopts an I -type unit cell, opposite to the calculated C -type (see Supplementary Discussion). As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Atomistic model calculations highlight the outstanding potential of high pressure experiments, as a plethora of polynitrogen entities have been predicted to be stable 1719 . Among them, the compression of magnesium and nitrogen was predicted to produce the MgN 3 , MgN 4 , and MgN 10 salts comprised of exotic anionic benzene-like N 6 rings, infinite 1D armchair chains and pentazolates, respectively 1719 . To the best of our knowledge, these predictions have not been tested until now.…”
Section: Introductionmentioning
confidence: 99%
“…[ 104,105 ] Three possible bonding modes were proposed, i.e., monodentate, bidentate, and metallocene‐like coordination. Recent first‐principles calculations combined with modern structure search algorithms have predicted a rich variety of crystal structures, such as in MN 5 (M = H, Na, and Cu), [ 30,34,106 ] MN 10 (M = Be, Ca, Mg, Ba, and Zn), [ 33,107–109 ] MN 15 (M = Al, Ga, Sc, and Y), [ 110 ] and IrN x ( x = 4, 7), [ 111 ] and estimated the synthesis conditions and energetic performance for many. These studies are critical, as they often serve to guide the experimental exploration of new materials, such as in the case of LiN 5 and CsN 5 .…”
Section: Nitrogen‐rich Compoundsmentioning
confidence: 99%
“…[ 28 ] The cyclo ‐N 5 − is a stable, aromatic, planar anion and has relatively large decomposition energy barrier of 117 kJ mol −1 , which shows the promise to obtain polynitrogen‐based HEDMs. In contrast to the extreme difficulty of isolating N 5 − at room conditions, studies have shown that N 5 − can be stabilized at high pressure in compounds such as LiN 5 , [ 29 ] NaN 5 , [ 30 ] CsN 5 , [ 31,32 ] MgN 10 , [ 33 ] and CuN 5 . [ 34 ] Moreover, N 5 3− is predicted to further aggregate and form higher oligomers or polymeric network in GaN 5 and GaN 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Therefore, a chain structure is formed by combining Mg and cyclo‐N 5 − that exists stably under ambient conditions, which is different from previous magnesium nitrides. [ 39–41 ]…”
Section: Figurementioning
confidence: 99%